2019
DOI: 10.1038/s41413-019-0059-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of GPCRs in bone diseases and dysfunctions

Abstract: The superfamily of G protein-coupled receptors (GPCRs) contains immense structural and functional diversity and mediates a myriad of biological processes upon activation by various extracellular signals. Critical roles of GPCRs have been established in bone development, remodeling, and disease. Multiple human GPCR mutations impair bone development or metabolism, resulting in osteopathologies. Here we summarize the disease phenotypes and dysfunctions caused by GPCR gene mutations in humans as well as by deletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 374 publications
(426 reference statements)
1
62
0
Order By: Relevance
“…For example, a 2019 review reported that there are presently 92 different GPCRs known to be involved in bone function and disease, including GPR120. This includes GPR120-mediated bone remodeling in OA [21,22]. Another study demonstrated the involvement of GPR120 activation in determining whether bone marrow mesenchymal stem cells differentiate into adipocytes or osteocytes [23].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a 2019 review reported that there are presently 92 different GPCRs known to be involved in bone function and disease, including GPR120. This includes GPR120-mediated bone remodeling in OA [21,22]. Another study demonstrated the involvement of GPR120 activation in determining whether bone marrow mesenchymal stem cells differentiate into adipocytes or osteocytes [23].…”
Section: Discussionmentioning
confidence: 99%
“…This gene encodes a cell membrane receptor that can regulate Wnt signaling and is implicated in both embryonic bone development and postnatal bone remodeling. (35) Rs10835153 and most of the other BMD-associated SNPs in this region were far downstream of LGR4 and closer to the littlestudied CCDC34 protein-encoding gene and to BBOX1-AS1 than to the LGR4 TSS ( Fig. 4C) but neither (36) for chromatin folding for the fetal lung fib cell line IMR-90; HMEC gave a similar profile (not shown).…”
Section: Npr3 Has Two Intergenic Bmd-risk Tier-1 Snps Upstream Of a Nmentioning
confidence: 83%
“…Thrombin is the natural ligand of F2r [40,41]. Currently, GPCRs remain a major target for bone related diseases drug discovery [38,39,42,43]. F2r has been the object of large-scale drug development programs since the 1990s, and Vorapaxar and drotrecogin-α are approved F2rtargeted therapeutics [20].…”
Section: Discussionmentioning
confidence: 99%